Intrinsic and Extrinsic Motivation of English Education Graduation Students Batch 2018 in Accomplishing Academic Performance - Elizabeth Elizabeth; Ouda Teda Ena (Institut Agama Islam Negeri Palopo, 2019)
This research is aimed to identify intrinsic and extrinsic motivation of graduate students in English Education Master Program batch 2018. However, motivation became the most dominant factor to build in relation to the academic performance. The research is limited to one research question “what are the factors of graduate students’ intrinsic and extrinsic motivation to build in relation to their academic performance?”. To answer the research question, the researcher employed descriptive qualitative research. The researcher conducted semi-structure interview with nine English Education graduate students. The participants are purposively selected. The result showed that intrinsic motivation is more dominant than extrinsic motivation to build in relation to the academic performance of English education graduate students batch 2018. In intrinsic motivation, the initial purpose or goal-oriented of English education graduated students batch 2018 for entering the college is the most dominant factor in order to build in relation to the academic performance. In extrinsic motivation, the role of supportive peers is higher than other characteristics of extrinsic motivation.